The On-Street Parking Premium and Car Drivers' Choice between Street and Garage Parking - Martijn Kobus; Eva Gutierrez Puigarnau; Piet Rietveld; Jos Van Ommeren (Tinbergen Institute, 2012)
We introduce a methodology to estimate the effect of parking prices on car drivers' choice between street and garage parking. Our key identifying assumption is that the marginal benefit of parking duration does not depend on this choice. The endogeneity of parking duration is acknowledged in the estimation procedure. We apply the methodology to an area where cruising for parking is absent, street parking is ubiquitous and garage parking is discretely located over space. So, in this area, the average distance to the final destination is longer for garage parking than for street parking. We find that drivers are willing to pay a premium for street parking which ranges from euro 0.35 to euro 0.58. Given a parking duration of one hour, we find that the demand for street parking is extremely price elastic: the price elasticity of demand for the share of street parking is -4. However, the price elasticity is much smaller for shorter parking durations. Our estimates imply that even small reductions in street parking prices induce a strong increase in the stock of cars parked on-street. Our estimates also imply that a policy which contains an on-street premium (so street prices exceed garage prices) is welfare improving, because drivers with longer parking durations are induced to use parking locations that are, on average, farther away.
urn:NBN:nl:ui:31-1871/38488
Keywords: R48; 330; street parking; garage parking; Ruhender Verkehr; Straßenbenutzungsgebühr; Willingness to pay; Preiselastizität; Niederlande